Índios & brasileiros : posse da terra Brasilis nos discursos jornalístico on line, político e indígena - Leal, Maria do Socorro Pereira (2011)
Our research brings to reflection and analysis the struggle over land in Brazil between Indians and Brazilians, as formulated in the journalistic discourse online, as well as in the political and indigenous discourses, to refer to indigenous land ownership. The main corpus consists of newspaper headlines from sites in three states: one of Roraima (www.folhabv.com.br Folha de Boa Vista), one of São Paulo (www.folhaonline.com.br Folha de São Paulo) and one of Rio de Janeiro (www.g1.com.br Globo Organizations); letters written by the political group of Roraima; and letters made by indigenous peoples. This work is based on the Discourse Analysis theoretical framework, as explained in various works of Michel Pêcheux, in France, and Eni Orlandi, in Brazil. The analysis was undertaken from a variety of themes that in the texts reviewed are linked to land belonging. This research attempts to infer how the ones engaged in the dispute over land, Indians and Brazilians, are designed throughout the discourse dispersion. The journalistic discourse online announces indigenous land ownership by a web of words and expressions that moves the issue into the realm of law, calling it illegal. The Indians' rights to land and voice do not appear in news headlines online. When the indigenous land ownership becomes news it is attached to negativity and losses related to all in Roraima, guiding meaning into a direction that makes Brazilians the legitimate land owners. In the Roraimense political discourse the indigenous land ownership is meant as a problem, since it is presented as an obstacle to the development of the state. As a result, the discursive construction of the reference of 'we' produces an effect of a totalizing homogeneity in relation to defense of property and diverse exploitation of land. The indigenous discourse presents, in the materiality of the language, various forms of resistance to the discourse about the Indians. The discursive constructions of the references of the Indians themselves and of those involved in the dispute over land issue follow another guideline: the indigenous discourse is not subject to the conciseness of the language, instead, it gives to see one-on-one of those included in the community.